Prevalence And Causes Of Maternal Mortality At A Tertiary Care Teaching Hospital In Western India (Indian Journal of Applied-Basic Medical Sciences, 2022)
Introduction: Maternal mortality is defined as the death of a woman while pregnant or within 42 days of termination of pregnancy irrespective of the duration and site of the pregnancy from any cause related to or aggravated by the pregnancy or its management, but not from accidental or incidental causes. The death of a mother has profound consequences on social and economic health and also on the development of a family and a nation. The objective of the current study is to determine the proportion of maternal mortality at our tertiary care teaching hospital, to analyse the epidemiological parameters and causes of maternal mortality, to determine the importance of antenatal, intranatal and postnatal care in relation to maternal mortality and to suggest preventive measures to reduce maternal mortality. Material and Methods: This retrospective observational study was carried out from 16th May 2018 to 15th December 2020 at a tertiary care teaching hospital. Results: Out of 15,164 deliveries, there were 15,006 live births. During the study period, 29 maternal deaths were recorded. Hence, Maternal Mortality Ratio (MMR) was 193.2. Majority, 12(41.4%) patients were in the age group of 21-25 years. Inadequate antenatal care was taken by 14 (48.3%) patients and 11 (37.9%) patients had not taken any antenatal care. Maternal mortality occurred in 12(41.3%) and 17(58.7%) patients during antenatal and postnatal period respectively. In 19(65.5%) patients, maternal mortality occurred due to direct obstetric causes and in 10 (34.5%) maternal mortality occurred due to indirect causes. Majority of mortality occurred due to delay in women seeking help. Conclusion: Majority of maternal mortality occurred due to delays at a community level in recognizing an emergency situation and/or delays in decision to seek care at a health facility. Community awareness regarding the importance of antenatal care, danger signs, high risk pregnancy, institutional deliveries, postnatal care and family planning can help in reducing maternal mortality by preventing delay at community level.
Keywords: maternal mortality; hypertensive disorders; sepsis